The Potential Coexistence of Autoimmune Thyroid Diseases and Pediatric Vulvar Lichen sclerosus - Agnieszka Dulska; Jakub Bodziony; Marta Janik; Agnieszka Drosdzol-Cop (MDPI AG, 2024)
Introduction: Vulvar lichen sclerosus (VLS), a chronic inflammatory skin disorder, often coexists with autoimmune thyroid disease (AITD). VLS presents with subtle symptoms including vulvar itching and discomfort. Clinically, a "Figure 8" pattern involving the labia minora, clitoral hood, and perianal region is often observed. It is prevalent both in pre-pubertal girls and women aged 40-60, and the link between VLS and AITD remains unclear, with proposed causes including autoimmune, hormonal or genetic factors, and environmental triggers. This study addresses the lack of research on the association in children, aiming to investigate the largest group of underage girls to date. Aim: This study aimed to investigate the coexistence of thyroid autoimmune diseases in girls diagnosed with vulvar lichen sclerosus (VLS) and to assess the presence of antibodies for specific thyroid autoimmune diseases. Materials and Methods: Our study was conducted from July 2020 to February 2021, involving a sample of 55 girls aged 2-18 years old, all free from systemic diseases. The study group comprised 20 girls previously diagnosed with vulvar lichen sclerosus (VLS), while the control group included 35 girls without VLS. Legal guardians completed questionnaires detailing the medical history of their children. Blood samples were collected from all participants and subjected to biochemical analysis. The presence of human IgG antibodies against thyroid peroxidase and IgG antibodies against thyroglobulin was assessed using the immunoenzymatic method with commercially available ELISA kits. Results: In the study group, common symptoms included itching, soreness, burning sensation, excoriation, and erythema or pallor of the skin and perineal mucosa. An evaluation of anti-thyroglobulin and anti-thyroid peroxidase antibodies revealed no statistical significance between the study and control groups (anti-TG p = 0.379, anti-TPO p = 0.96). Family history of autoimmune diseases showed no significant correlation with anti-thyroid antibodies in girls. Although no significant relation between VLS occurrence and antibody levels was found, it emphasizes the need for multidisciplinary medical care. Further research with larger patient groups is necessary.